Genesa Tanah yang Berkembang pada Puncak Gunung Sumbing - Hizkia Setya Simangunsong; Djoko Mulyanto; Partoyo Partoyo (UNIVERSITAS LABUHANBATU, 2022)
The process of forming soil at the top of the cleft mountain is an attractive polygenesis phenomenon observed. Genesis and soil classification can be used as a reference for land management and the environment in the observer area. The purpose of the study was to determine the process of genesis and the classification of land. The research was conducted descriptive method and survey, namely field analysis for morphology and environmental circumstances, then laboratory analysis included H2O pH, NAF, C-organic, KPK and Kesan and Kesan (CA, MG, K, and NA), alkaline saturation, retention-p , land texture, and mineral sand fraction. The results of the study show that the soil that developed on the summit of the cleft mountain is an undeveloped soil which is further marked by high-weathered minerals, based on the classification of land according to the USDA taxonomy is Acrudoxic Ultic Hapludands, according to the national land classification is Andosol Umbrik and according to the World Reference Base for Soil Resources Andosols Umbric Thixotropic. Land experienced polygenesis with the presence of Buried Soil and having had weather weathering was still low due to low temperatures. Keywords: genesis, mount Sumbing, soil classification, soil formation